High Plasma Soluble CD163 During Infancy Is a Marker for Neurocognitive Outcomes in Early-Treated HIV-Infected Children - Benki-Nugent, Sarah F.; Martopullo, Ira; Laboso, Tony; Tamasha, Nancy; Wamalwa, Dalton C.; Tapia, Kenneth; Langat, Agnes; Obimbo, Elizabeth Maleche; Marra, Christina M.; Bangirana, Paul; Boivin, Michael J.; Stewart, Grace C. John (Journal of acquired immune deficiency syndromes, 2019)
Monocyte activation may contribute to neuronal injury in aviremic HIV-infected adults; data are lacking in children. We examined the relation between monocyte activation markers and early and long-term neurodevelopmental outcomes in early-treated HIV-infected children.Prospective study of infant and child neurodevelopmental outcomes nested within a randomized clinical trial () and extended cohort study in Kenya.HIV-infected infants (N=67) initiated ART at age <5 months. Plasma soluble (s) CD163 (sCD163), sCD14 and neopterin were measured pre-ART (entry) and 6 months later. Milestone attainment was ascertained monthly during 24 months and neuropsychological tests (NPTs) were performed at 5.8–8.2 years post-initiation of ART (N=27). The relationship between neurodevelopment and sCD163, sCD14 and neopterin at entry and 6 months post-ART was assessed using Cox proportional hazards models and linear regression.Infants with high entry sCD163 had unexpected earlier attainment of supported sitting (5 vs 6 mo.; P=0.006) and supported walking (10 vs 12 mo.; P =0.02) with trends in adjusted analysis. Infants with high 6-month post-ART sCD163 attained speech later (17 vs 15 mo.; P=0.006; aHR, 0.47; P=0.02), threw toys later (18 vs 17 mo.; P =0.01; aHR, 0.53; P =0.04), and at median 6.8 years post-ART, had worse NPT scores (adj. mean z-score differences, cognition, −0.42; P =0.07; short-term memory, −0.52; P =0.08; nonverbal test performance, −0.39, P =0.05).Prior to ART, monocyte activation may reflect transient neuroprotective mechanisms in infants. Following ART and viral suppression, monocyte activation may predict worse short- and long-term neurodevelopment outcomes.
Keywords: monocyte, neurocognitive, antiretroviral, perinatal HIV, CD163, neurodevelopment